Filsafat Pendidikan Islam dalam Membangun Masyarakat Berkarakter Islami: Pendekatan Nilai dan Moral - Nazifah Fitri Annisa; M. Wahyu Fahrizal; Herlini Puspika Sari (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2025)
This article discusses the role of Islamic educational philosophy in shaping an Islamic-character society through values and moral approaches. Islamic education emphasizes not only knowledge transfer but also character building based on religious values. The integration of Islamic values and morals in education is expected to foster a generation that is knowledgeable and morally upright, contributing positively to society. This article also highlights the importance of the roles of educators, families, and communities in creating an environment that supports Islamic character education. This synergy is hoped to develop individuals capable of facing modern challenges grounded in solid religious values.